Negotiation in Academic Medicine: Narratives of Faculty Researchers and Their Mentors - Sambuco, Dana (2013)
PURPOSE: Few researchers have explored the negotiation experiences of academic medical faculty even though negotiation is crucial to their career success. The authors sought to understand medical faculty researchers' experiences with and perceptions of negotiation. METHOD: Between February 2010 and August 2011, the authors conducted semi-structured, in-depth telephone interviews with 100 former recipients of National Institutes of Health mentored career development awards and 28 of their mentors. Purposive sampling ensured a diverse range of viewpoints. Multiple analysts thematically coded verbatim transcripts using qualitative data analysis software. RESULTS: Participants described the importance of negotiation in academic medical careers but also expressed feeling naïve and unprepared for these negotiations, particularly as junior faculty. Award recipients focused on power, leverage, and strategy, and they expressed a need for training and mentorship to learn successful negotiation skills. Mentors, by contrast, emphasized the importance of flexibility and shared interests in creating win-win situations for both the individual faculty member and the institution. When faculty construed negotiation as adversarial and/or zero-sum, participants believed it required traditionally masculine traits and perceived women to be at a disadvantage. CONCLUSIONS: Academic medical faculty often lack the skills and knowledge necessary for successful negotiation, especially early in their careers. Many view negotiation as an adversarial process of the sort that experts call “hard positional bargaining.” Increasing awareness of alternative negotiation techniques (e.g., “principled negotiation,” in which shared interests, mutually satisfying options, and fair standards are emphasized), may encourage the success of medical faculty, particularly women.